The Effectiveness of Using Python-Based Interactive Games in Improving Student Motivation and Learning Outcomes - Amril Samosir; Rizki Agung Wibowo; Tyan Tasa (Information Technology and Science (ITScience), 2026)
This study aims to analyse the effectiveness of using Python-based interactive games in improving student motivation and learning outcomes. The method used was Research and Development (R&D) based on the ADDIE model. The research design employed a One-Group Pretest-Posttest Design with 60 students as subjects. The research instruments consisted of a learning outcome test and a Likert-scale learning motivation questionnaire. Data analysis utilised descriptive statistics, N-Gain calculations, and a Paired Sample t-Test. The results showed that the average pre-test score of 67.01 increased to 82.40 on the post-test, representing a gain of 15.39 points. The learning motivation score rose from 70.85 to 82.99, an increase of 12.14 points. The N-Gain value of 0.47 falls into the moderate category. Statistical tests revealed a significant difference between pre- and post-intervention scores. These findings indicate that Python-based interactive games effectively enhance motivation and learning outcomes whilst supporting digital learning innovation